TRAIL-based tumor sensitizing galactoxyloglucan, a novel entity for targeting apoptotic machinery. (February 2015) - Aravind, S.R.; Joseph, Manu M.; George, Suraj K.; Dileep, K.V.; Varghese, Sheeja; Rose-James, Alphy; Balaram, Prabha; Sadasivan, C.; Sreelekha, T.T.
Graphical abstract: Highlights: Morphological evaluation proved that PST001 induces apoptosis in cancer cells. PST001-induced apoptosis was evidenced by the increase in Annexin V positive cells. Microarray and TLDA analysis suggested PST001 acts via TRAIL/TNF pathway. In silico studies also confirmed that PST001 acts via TRAIL pathway. PST001 has the potential to be developed as a TRAIL-specific anti-cancer agent. Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is an attractive target for cancer therapy due to its ability to selectively induce apoptosis in cancer cells, without causing significant toxicity in normal tissues. We previously reported that galactoxyloglucan (PST001) possesses significant antitumor and immunomodulatory properties. However, the exact mechanism in mediating this anticancer effect is unknown. This study, for the first time, indicated that PST001 sensitizes non-small cell lung cancer (A549) and nasopharyngeal (KB) cells to TRAIL-mediated apoptosis. In vitro studies suggested that PST001 induced apoptosis primarily via death receptors and predominantly activated caspases belonging to the extrinsic apoptotic cascade. Microarray profiling of PST001 treated A549 and KB cells showed the suppression of survivin (BIRC5) and anti-apoptotic Bcl-2, as well as increased cytochrome C. TaqMan low density array analysis of A549 cells also confirmed that the induction of apoptosis by the polysaccharide occurred through the TRAIL-DR4/DR5 pathways. This was finally confirmed by in silico analysis, which revealed that PST001 binds to TRAIL-DR4/DR5 complexes more strongly than TNF and Fas ligand–receptor complexes. In summary, our results suggest the potential of PST001 to be developed as an anticancer agent that not only preserves innate biological activity of TRAIL, but also sensitizes cancer cells to TRAIL-mediated apoptosis.